DEVELOPING TPACK OF EFL TEACHERS IN ISLAMIC BOARDING SCHOOLS THROUGH A TPACK-BASED COURSE - Dias Tiara Putri Utomo; Diah Eko Martini; Hardianti Hardianti (TEFLIN Journal)
Numerous studies have delved into TPACK framework integration in EFL regular classrooms, but less studies have researched its implementation in an Islamic boarding school setting. This study aims to investigate the impact of a TPACK-based course on the understanding and application of TPACK of EFL teachers in Islamic boarding schools in the Indonesian context. This qualitative study was conducted within six months from July 2024 to December 2024. The participants were four female EFL teachers at two Islamic boarding schools in Lamongan, East Java, Indonesia. This study collected data from multiple sources, including classroom observations, interviews, documents, and audiovisual materials. The research findings reveal that the course positively impacted teachers’ TPACK development, especially in terms of technological domains and the teachers’ ability to integrate technology into their teaching. Furthermore, the course has fostered a shift from traditional, teacher-centered practices to more dynamic, student-centered approaches. While barriers such as limited access to resources and lacks of creativity and innovation in utilizing technology posed challenges, the teachers’ increased confidence in using digital tools and their proactive approach to overcoming obstacles were clear indicators of the course’s success.